Промышленная электроника: [учеб. пособие] / Забродин Ю. С. - Забродин Ю. С. (Высшая школа, 1982)
Экземпляры: КХ (20060123) / Инвентарный номер: 787477 / Сис.шифр: 621.38 / Авт.знак: З-12 / ГРНТИ: 47 / ББК: 3